Radiologic Evaluation of the Prechiasmatic Sulcus in Adults and Clinical Implications - Beger, Orhan; Bahşi, İlhan and Seda Adanır, Saliha and Orhan, Mustafa and Kervancıoğlu, Piraye and Didem Yalçın, Eda (ENT Updates, 2021)
Background: The present work intended to analyze the prechiasmatic sulcus types in adults via cone-beam computed tomographic images. Methods: Four hundred randomly selected adult patient files registered in the electronic system of Gaziantep University Faculty of Dentistry were investigated retrospectively. The morphological features of the prechiasmatic sulcus including its size, angulation, and classification were revealed. Results: The planum length was measured as 11.82±3.12 mm (4.70-20.72 mm), the sulcal length as 5.61±1.50 mm (1.82-11.20 mm), the sulcal angle (SA) as 18.66±9.90˚ (0-50.60˚), and the interoptic distance as 17.65±2.14 mm (8.60-24.52 mm). The interoptic distance was greater in male samples compared to females (P < .001); however, the sulcal angle (P = .834), sulcal length (P = .658), and planum length (P = .326) were similar in genders. Considering the average groove length and angle, the narrow steep sulcus was observed as 22.25% (89 cases), the narrow flat sulcus as 26.75% (107 cases), the wide steep sulcus as 25.5% (102 cases), and the wide flat sulcus as 25.5% (102 cases). Conclusions: The findings of this radiologic study may be helpful for neurosurgeons, neuroradiologists, and otorhinolaryngologists in selection of patients suitable for surgical approach (e.g., endonasal or transcranial), by providing categorization of the prechiasmatic sulcus during resection of sulcus-related pathological entities.